ISAR imaging using circularly polarized antennas in an anechoic chamber - Baharuddin M.Z.B.; Izumi Y.; Sumantyo J.T.S.; Demirci S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Anechoic chambers; Antennas; Circular polarization; Electric network analyzers; Image enhancement; Image processing; Inverse synthetic aperture radar; Polarimeters; Polarization; Radar; Radar antennas; Radar astronomy; Scattering parameters; Synthetic aperture radar; Circularly polarized; Circularly polarized antennas; Controlled environment; Inverse synthetic aperture radars (ISAR); Measurement procedures; Polarimetric decomposition; Radar polarimetry; Vector network analyzers; Radar imaging